Supplementation With Whey Peptide Rich in β-Lactolin Improves Cognitive Performance in Healthy Older Adults: A Randomized, Double-Blind, Placebo-Controlled Study - Kita, Masahiro; Kobayashi, Keiko; Obara, Kuniaki; Koikeda, Takashi; Umeda, Satoshi; Ano, Yasuhisa (Frontiers in Neuroscience, 2019)
Epidemiological reports showed that consumptions of fermented dairy products are beneficial for cognitive decline in elderly. Our previous preclinical studies have demonstrated that intakes of whey peptide rich in the β-lactolin [β-lactopeptide of glycine-thereonine-tryptophan-tyrosine (GTWY)] improve memory and attention by regulating monoamine system, and clinical study using neuropsychological test suggested that consumptions with GTWY-rich whey peptide enhance cognitive performance associated with the frontal cortex activity. However, corresponding interventional studies in humans are limited. Objectives: to evaluate the effects of the whey peptide on cognitive functions in healthy older adults using a randomized, double-blinded, placebo-controlled trial design. 114 healthy subjects aged 50–75 were supplemented with the whey peptide or placebo for 12 weeks, and changes in cognitive function were assessed using neuropsychological tests at weeks 0, 6, and 12 of the intervention. Neuropsychological tests included assessments for memory functions (subtests from Wechsler memory scale-revised, standard verbal paired-associate learning test, and recognition memory test for faces), assessments for attention (cancelation and detection tests), and assessments for general cognitive functions (repeatable battery for assessments of neuropsychological status). Cerebral blood flow was also assessed using near-infrared spectroscopy (NIRS) after 6 weeks of intervention. This study was registered on the 19 November, 2017 in the database of the University Hospital Medical Information Network (UMIN) prior to enrollment of subjects (Registration No. UMIN000030461: https://www.umin.ac.jp/ctr/index-j.htm). In the whey peptide group, visual paired-associates I and visual cancelation tests were significantly improved compared with those in the placebo group at weeks 6 and 12 of the intervention, respectively. Visuospatial and constructional scores of the repeatable battery for assessments of neuropsychological status and standard verbal paired-associate learning tests (S-PA) also tended to be improved by the intervention at week 12. Daily intakes of GTWY-rich whey peptide show beneficial effects on cognitive performance, especially associative learning memory and control of attention, in healthy older adults and might prevent age-related cognitive declines.